The Power of Schadenfreude: Predicting Behaviors and Perceptions of Trolling Among Reddit Users - Pamela Jo Brubaker (Social Media + Society, 2021)
Trolling is an uncivil behavior that is increasingly prevalent in online social interactions. This study sought to understand trolling by examining the psychological predictors that motivate trolling behaviors, as well as perceptions of trolling among 438 Reddit users. A path analysis indicated the motivation of schadenfreude mediates the relationship between personality traits (i.e., the dark triad) and trolling. Outspokenness neither directly nor indirectly predicted trolling. Results also showed that Reddit users motivated by schadenfreude and users who exhibit trolling behaviors view trolling as not being a dysfunctional or undesirable response to online discourse. In addition, those with schadenfreude considered the practice of trolling to be functional/comprehensible. Those who merely observe trolling on Reddit did not consider trolling to be a functional part of online discourse. Age, time spent on Reddit, and the dark triad did not predict functional or dysfunctional perceptions of trolling, but gender played a role.